Positive growth and redemption in prison: finding light behind bars and beyond - Kazemian, Lila (International series on desistance and rehabilitation, 2020)
"Drawing on an original longitudinal study of French prisoners, this book assesses the similarities and differences in prison experiences across different cultural settings, considers life course transitions, fluctuations in psychological well-being, and whether what we know about desistance can be applied to those incarcerated"--